Microhardness, corrosion behaviour and microstructures of directionally solidified Al-Cu alloys - Ares, Alicia Esther (2013)
The aim of this work is to analyze the effect of microstructural parameters (secondary dendritic arm spacings) on the microhardness and corrosion behavior of hypoeutectic Al-Cu alloys. Experimental results include HV microhardness values, corrosion and pitting potential and current density. It was found that high cooling rates during solidification provide finer dendritic spacings, which encourage better mechanical properties. The Vickers microhardness increases as the contents of copper in the alloy increases. The most influencing microstructural variable for corrosion resistance has been found to be the secondary dendrite arm spacing. It has been found that that corrosion resistance decreases with the increasing in secondary spacing until 10wt.% of Cu.